Conceptual Profiles: Theoretical-methodological Grounds and Empirical Studies. (8th January 2015) - El-Hani, Charbel N.; Amaral, Edênia Maria Ribeiro do; Sepulveda, Claudia; Mortimer, Eduardo F.
Abstract: In this paper, we briefly address the theoretical and methodological grounds of the conceptual profile theory and discuss two empirical studies aiming at constructing conceptual profile models and using them to analyze classroom discourse in different sciences, chemistry (entropy and spontaneity) and biology (adaptation). The basic idea is to illustrate how these models were built, considering differences and similarities between the methods used for this purpose. Conceptual profiles are models of different modes of seeing and conceptualizing the world used by individuals to signify their experience. They are built for a given concept and are constituted by several zones, each representing a particular mode of thinking about that concept, related to a particular way of speaking. Each zone is individuated by ontological, epistemological, and axiological commitments underlying discourse. We will show how different concepts, situated in sciences with different levels of conceptual polysemy, demand different methodologies to deal with the variation found in meaning making in the sociocultural, ontogenetic, and microgenetic domains.